2002
DOI: 10.1021/ic0109400
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Electronic Effect of Substituted Phosphine Ligands via Molecular Electrostatic Potential

Abstract: Values of the molecular electrostatic potential minimum (V(min)) corresponding to the lone pair region of several substituted phosphine ligands (PR(3)) have been determined at the DFT level. The V(min) value is proposed as a quantitative measure of the electronic effect of the PR(3) ligands. Good linear correlation between V(min) and Tolman electronic parameter of PR(3) has been obtained. V(min) is also proportional to the pK(a) values of the conjugate acids of PR(3), viz., [PR(3)H](+). Further, the DeltaE val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
153
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(156 citation statements)
references
References 43 publications
1
153
0
2
Order By: Relevance
“…11 Crabtree et al reported a scheme for quantifying the electronic impact of different phosphines using ab initio calculations on Ni(CO) 3 (PR 3 ) complexes. 12 Koga et al 13 focused on PR 3 ligands in order to develop metal-independent measures of electronic character. Pittard and co-workers used PM3(tm) quantum mechanics to evaluate semiempirical electronic parameters (SEP) for phosphines ligated to Mo(CO) 5 (PR 3 ), W(CO) 5 (PR 3 ), and CpRh(CO)(PR 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…11 Crabtree et al reported a scheme for quantifying the electronic impact of different phosphines using ab initio calculations on Ni(CO) 3 (PR 3 ) complexes. 12 Koga et al 13 focused on PR 3 ligands in order to develop metal-independent measures of electronic character. Pittard and co-workers used PM3(tm) quantum mechanics to evaluate semiempirical electronic parameters (SEP) for phosphines ligated to Mo(CO) 5 (PR 3 ), W(CO) 5 (PR 3 ), and CpRh(CO)(PR 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In numerous studies pursuing the efficient synthesis of Ph-SMAP (1a) (the parent compound for various SMAP-type compounds), we have developed a route that uses benzylphosphine (12) as a source of the P atom as shown in Scheme 1. Thus, phenyltrivinylsilane (10), which was prepared from PhSiCl 3 and vinylmagnesium bromide, was converted into tribromide 11 through anti-Markovnikov HBr addition.…”
Section: Synthesismentioning
confidence: 99%
“…12 A larger negative V min value corresponds to a stronger electron-donating ability of a phosphine. The V min (∫43.14 kcal/mol) of Ph-SMAP is much more negative than the value of monoaryldialkylphosphine PhMe 2 P and is in the range for trialkylphosphines, being between the values of Me 3 P and Et 3 P (see also Figure 8).…”
Section: Structure and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We optimized the geometry of Ph-SMAP ( Figure 4a) and evaluated donor ability by the value of the molecular electrostatic potential minimum V min (kcal·mol -1 ) according to Koga's method. 18 A larger negative V min value corresponds to stronger electron-donating ability of a phosphine. For comparison, we also performed calculations for 4-phenyl-1-phosphabicyclo[2.2.2]octane (13, Figure 4b), an analog of Ph-SMAP that has a bridgehead carbon atom instead of the Si atom.…”
Section: Electronic Properties Of Ph-smap (Dft Calculations)mentioning
confidence: 99%